The Correlation Between Independence Levels and The Efforts to Fulfi ll Personal Hygiene of Elderly in Panti Sosial Tresna Werdha (PSTW) Abiyoso Pakem Sleman Yogyakarta - Sigit Priyanto (IJNP (Indonesian Journal of Nursing Practices), 2014)
Background: Entering elderly age, a person will experience many physical, mental and social declining. Elderly people will experience deterioration of the independence so that they will require help from others to meet their needs. Requirement that is usually overlooked is the personal hygiene which is one of the basic needs that must be met by every human being.Objective: The research aimed to determine the correlation between the level of independence and the fulfi llment of personal hygiene of the elderly in PSTW Abiyoso Yogyakarta.Methods: The method used was cross sectional survey with a sample of 49 respondents. Outcome measure: The instrument used was a questionnaire. The data was processed by using the Spearman rank statistical test.Results: The result showed that there was a correlation between the level of independence and the eff ort to fulfi ll the personal hygiene of the elderly in PSTW Abiyoso Yogyakarta, with the results’ signifi cant value = 0.001 (p 0,05).Conclusion: there was a correlation between the level of independence and the eff ort to fulfi ll the personal hygiene of the elderly in PSTW Abiyoso Yogyakarta.Keywords: elderly, independence, personal hygiene